Associação entre o achado de cárdia incompetente à endoscopia digestiva alta e presença de esofagite de refluxo - Machado, Wellington Monteiro [UNESP]; Xavier, Marcela Vieira; Neto, Pedro Padula; Padovani, Carlos Roberto [UNESP] (My University, 2005)
Incompetent cardia (IC) or loose cardia is not uncommon at endoscopic examination but its meaning is not clear. Such incompetence could facilitate gastroesophageal reflux and the appearance of esophagitis as a consequence. The aim of this study is to investigate if there is an association between IC and reflux esophagitis (RE). A review was made of 395 consecutive endoscopic reports of adult males and females performed at the Botucatu Clinics Hospital, of the Unesp - University of the State of São Paulo. Diagnosis of IC is defined by the endoscopic image in which the cardia is partially opened and/or involves the endoscope in a loose manner. Esophagitis characterization was based in the Los Angeles classification. The statistical analysis showed a significant association between CI and RE (p < 0.0001). Although there is not a clear explanation for this association, some hypotheses could be suggested involving hypotonic LES, diaphragmatic crura ineffectiveness and TLESR disorders as conditions able not only to keep the cardia relaxed but also to the reflux followed by esophagitis.
Association between the finding of incompetent cardia at endoscopic examination and the presence of reflux esophagitis
Keywords: Incompetent cardia; Loose cardia; Reflux esophagitis; adult; Brazil; diaphragm; endoscopy; female; gastroesophageal reflux; human; lower esophagus sphincter; major clinical study; male; muscle hypotonia; reflux esophagitis; retrospective study